Late complications in patients with intestinal ostomies who underwent a preoperative site marking (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: Describe late complications related to intestinal ostomies in patients undergoing a preoperative site marking. Method: Descriptive study with a quantitative approach. The convenience sample and was composed of 15 people with intestinal ostomies who underwent a preoperative site marking. Data collection was performed between January and March 2014 through a pre-established script that guided the physical examination and a questionnaire containing 13 questions related to the sociodemographic profile, diagnosis, and preoperative site marking. Results: It was verified that in 13 (87.7%) people who had site marked ostomies, it was located at a distance of more than 5 cm of surgical scars, iliac crest, umbilical scar, and waistline. Two people with ileostomy (13.3%) had intestinal loop protrusion short of recommended. Regarding postoperative complications, three participants (20%) presented peristomal dermatitis and one (6.7%), in addition to dermatitis, prolapse of the ostomy. Conclusion: The study showed that the postoperative complications reported by patients who underwent a preoperative stomatal site marking were poorly observed and that these was consisted of peristomal dermatitis and prolapse of the ostomy.
Keywords: Ostomy; Preoperative site marking; Post-Operative Complications; Nursing; Stomatherapy.